Pancreatectomy With Arterial Resection for Pancreatic Adenocarcinoma: How Can It Be Done Safely and With Which Outcomes?. Issue 5 (May 2020) - Bachellier, Philippe; Addeo, Pietro; Faitot, François; Nappo, Gennaro; Dufour, Patrick
Abstract : Objective: This study assesses the safety and outcomes of the largest cohort of pancreatectomy with arterial resection (P-AR). Background: A high postoperative mortality rate and uncertain oncologic benefits have limited the use of P-AR for locally advanced pancreatic adenocarcinoma. Methods: We retrospectively reviewed a prospectively maintained database of patients who underwent P-AR between January 1990 and November 2017. Univariate and multivariate Cox analyses were used to assess prognostic factors for survival. Results: There were 118 consecutive resections (51 pancreaticoduodenectomies, 18 total pancreatectomies, and 49 distal splenopancreatectomies). Resected arterial segments included the coeliac trunk (50), hepatic artery (29), superior mesenteric artery (35), and other segments (4). The overall mortality and morbidity were 5.1% and 41.5%, respectively. There were 84 (75.4%) patients who received neoadjuvant chemotherapy, 105 (89%) simultaneous venous resections, and 101 (85.5%) arterial reconstructions. The rates of R0 resection and pathologic invasion of venous and arterial walls were 52.4%, 74.2%, and 58%, respectively. The overall survival was 59%, 13%, and 11.8% at 1, 3, and 5 years, respectively. The median overall survival after resection was 13.70 months (CI 95%:11–18.5 mo). In multivariate analysis, R0 resection (HR: 0.60; 95% CI: 0.38–0.96; P = 0.01) and venous invasion (HR: 1.67; 95% CI: 1.01–2.63; P = 0.04) were independent prognostic factors. Conclusion: In a specialized setting, P-AR for locally advanced pancreatic adenocarcinoma can be performed safely with limited mortality and morbidity. Negative resection margin and the absence of associated venous invasion might predict favorable long-term outcomes.